KETERBACAAN TEKS DALAM BUKU SISWA KELAS VI SEKOLAH DASAR - Imam, Muhammad Choirul (Universitas Negeri Surabaya, 2018)
ABSTRACTThis research purposed to describe the readability tex in the six grade book. This purpose atributed with three manners for analyzing readability levels, tes of question and answer, readability formula, and cloze tes. This research diversified quantitative-qualitative by descriptive method. This research subject was twenty seven text from nine theme, also student in Lamongan The Elementary School of Paciran 1. To collect data, used documentation technique (Fry Graph), also word association test, and cloze test. The data of Fry Graph, word association test, and cloze tes taken from the described score taken from describe the parts. The result of this research is first, the readability text based on early knowledge of readers about topics were difficult because of the percentage result from the test of word association were 29%. Second, the readability tekt based on the readability levels based on readability formula(Fry Graph) is 7, 8, dan 9 also very close long word area. Third, the readability text based on the vocabularies control which was influenced by the language knowledge student was difficult because of the percentage result from Cloze test was 10%. Therefore, teks in The Six Grade Book was difficulted to readable and comprehended student class VI because the quality text based on long-short word, knowledge readers (early and vocabularies control) and Cloze test was difficult. Keywords: Readability Teks, Word Association Tes, Fry Graph, Cloze Tes. ABSTRAK Penelitian ini bertujuan mendeskripsikan tentang keterbacaan teks yang termuat dalam buku siswa kelas VI. Tujuan tersebut juga terkait dengan tiga cara untuk menganalisis tingkat keterbacaan, yakni tes tanya jawab, formula keterbacaan dan tes Cloze. Penelitian ini berjenis kualitatif-kuantitatif dengan metode deskriptif. Subjek penelitian ini adalah dua puluh tujuh teks dalam sembilan tema, serta siswa di SD Negeri Paciran I Lamongan. Untuk mengumpulkan data, digunakan teknik dokumentasi (Grafik Fry) serta tes asosiasi kata dan tes Cloze. Data dari Grafik Fry, tes asosiasi kata, dan tes Cloze berupa skor yang dideskripsikan serta data dari analisis berupa deskripsi. Hasil penelitian ini pertama, tingkat keterbacaan teks berdasarkan pengetahuan awal pembaca tentang topik adalah rendah karena hasil presentasi tes asosiasi kata 29%. Kedua, tingkat keterbacaan teks berdasarkan formula keterbacaan (Grafik Fry) adalah 7, 8, dan 9 serta mendekati daerah long word. Ketiga, tingkat keterbacaan berdasarkan tes Cloze yang dipengaruhi oleh pengetahuan kebahasaan siswa itu sulit karena hasil persentase tes Cloze 10%. Dengan demikian, teks dalam buku teks kelas VI sulit dibaca dan dipahami siswa kelas VI karena kualitas teks berdasarkan pengetahuan siswa, panjang-pendek, dan tes Cloze tergolong sulit. Kata Kunci: Tingkat Keterbacaan Teks, Asosiasi Kata, Grafik Fry, Tes Cloze